(3x-12)(2x+9)=0

If any individual factor on the left side of the equation is equal to 0, the entire expression will be equal to 0.

3x-12=0

2x+9=0

Set the first factor equal to 0.

3x-12=0

Add 12 to both sides of the equation.

3x=12

Divide each term by 3 and simplify.

Divide each term in 3x=12 by 3.

3×3=123

Cancel the common factor of 3.

Cancel the common factor.

3×3=123

Divide x by 1.

x=123

x=123

Divide 12 by 3.

x=4

x=4

x=4

Set the next factor equal to 0.

2x+9=0

Subtract 9 from both sides of the equation.

2x=-9

Divide each term by 2 and simplify.

Divide each term in 2x=-9 by 2.

2×2=-92

Cancel the common factor of 2.

Cancel the common factor.

2×2=-92

Divide x by 1.

x=-92

x=-92

Move the negative in front of the fraction.

x=-92

x=-92

x=-92

The final solution is all the values that make (3x-12)(2x+9)=0 true.

x=4,-92

Solve using the Square Root Property (3x-12)(2x+9)=0